The Continuous Dependence and Numerical Approximation of the Solution of the Quasilinear Pseudo-Parabolic Problem with Periodic Boundary Condition - Kanca, Fatma; Baglan, Irem Sakinc (JOURNAL OF ADVANCES IN MATHEMATICS, 2014)
In this paper we consider a pseudo- parabolic equation with a periodic boundary condition and we prove the stability of a solution on the data. We give a numerical example for the stability of the solution on the data.